The Contribution of Water and Sunlight to the Lettuce Production - La Ode Amaluddin; Hildayanti Hildayanti; Rosliana Eso; Rahma Musyawarah; Agus Sugiarto; Rajendra Prasad Shrestha; Muhammad Isa Ramadhan; Andri Estining Sejati (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2023)
Indonesian lettuce production is still lower than consumption.Lettuce production in Indonesia is still low because hydroponiccultivation needs more concern with the water and sunlight factors.This first study aimed to determine the contribution of water andsunlight to the growth of lettuce. The second study aimed to find outthe difference in lettuce production between the difference in waterand sunlight conditions. This research used the experimentalmethod. The research was conducted in a field laboratory andhydroponic village at the Faculty of Agriculture, Halu OleoUniversity. Data collection methods using field observations andmeasurements. The first objective data analysis techniquesdescribed water quality and sunlight measurements. The secondobjective data analysis used a description of the result of the lettucevariable costing. The results showed that water and sunlightcontributed to the production of lettuce. The water adds nutrients,and the sunlight does not direct to lettuce-affected plants, whichtend to have broad and healthy leaves. The good water and sunlightconditions contribute to pressing the cost of maintaining plants andraising the profit from lettuce production. These results areimportant to the attention of the water and sunlight conditions thatcan raise lettuce production in Indonesia